Hukum Keluarga Kontemporer di Negara India dan Pakistan - Rida Maryani Iryanti; Muhamad Husni Alghiffari; Dina Triana Febriana (CV Rewang Rencang, 2025)
The renewal of family law carried out by various Muslim countries generally includes three main aspects, namely marriage, divorce, and inheritance. In the context of marriage, one form of renewal that is implemented is marriage registration. This stage is considered important because it aims to create order in marriage in society, maintain the sanctity of marriage, and specifically protect women's rights in domestic life. This paper discusses the reform of Islamic law, especially in the field of family law, in the legal systems of India and Pakistan. These two countries are discussed together because they have the same historical background, namely that it was once a territory under British rule before Pakistan seceded and became the Islamic Republic of Pakistan. Through a literature study, the study found that India and Pakistan implemented family law reform with a moderate approach, not as liberal as some other Muslim countries. The main findings of this paper reveal that the reform of Islamic family law in both countries has many similarities. This is most likely influenced by their history as a unit before independence and the similarity in the majority of its population adhering to the Hanafi school.